2020
DOI: 10.1186/s12891-020-03318-x
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, functional and radiographic outcomes of primary total hip arthroplasty between direct anterior approach and posterior approach: a systematic review and meta-analysis

Abstract: Background: The purpose of this systematic review and meta-analysis was to compare the direct anterior approach and posterior approach for primary total hip arthroplasty in terms of the clinical, functional and radiographic outcomes. Methods: We searched the PubMed and EMBASE databases and Cochrane Library from their inception to November 1, 2019. We searched for previously published articles and meta-analyses of randomized controlled trials. Results: A total of 7 randomized controlled trials with 600 particip… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
1
20
0
2
Order By: Relevance
“…Although the confidence interval of our interobserver variation for stem alignment was large, the difference in degrees was low and not clinically relevant. Comparable results were seen in the study by Lin et al [64] However, no differences were seen in another randomized trial and two recent meta-analyses and desired angles can be achieved in both approaches [11,12,65]. We observed two patients with a dislocation, one in each group.…”
Section: Discussionsupporting
confidence: 56%
“…Although the confidence interval of our interobserver variation for stem alignment was large, the difference in degrees was low and not clinically relevant. Comparable results were seen in the study by Lin et al [64] However, no differences were seen in another randomized trial and two recent meta-analyses and desired angles can be achieved in both approaches [11,12,65]. We observed two patients with a dislocation, one in each group.…”
Section: Discussionsupporting
confidence: 56%
“…The main reasons that result in LFCN injury include two aspects: ① the anatomical variations and frequent branches of LFCN; ② the DAA approach close to the path of LFCN. In the proximal femur, LFCN courses the intermuscular space between the TFL and sartorius muscles, which is also the surgical field [ 17 , 24 , 25 ]. These two factors increase the risk of cutting or suturing of LFCN interoperation, which are the main reasons for LFCN injury.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates a longer operative time and shorter length of incision for DAA-THA compared with PLA-THA. Recently, two literature reviews showed that DAA requires a longer operative time than PLA in THA [ 27 , 28 ]. We believe that the prolonged operative time in DAA is mainly related to the difficulty of proximal femur exposure because of the need for gradual release, exposure, and the additional steps, all of which result in a longer operative time in DAA than in PLA.…”
Section: Discussionmentioning
confidence: 99%